Development of mathematical model for muscle activity, psychophysical experience and heart rate during manual load carrying - Zahri, Nuradilah (2017)
Manual materials handling (MMH) were categorized as highly risk physical activities if improperly conducted. As found in previous research, numbers of work-related musculoskeletal disorder (WRMSD) increased among the industrial workers caused by MMH. Hence, this research aims to find risk factors and its effect towards changes in muscle activity, heart rate, and psychophysical experience which specifically associated with manual load carrying activities. Mathematical models were develop to express the relationship between the risk factors towards muscle activity, heart rate, and psychophysical experience. Thirty subjects were asked to carry a load mass of water bottles while walking on certain distances on flat and inclination surfaces. Results revealed that load mass had significantly affected muscle activity and increased rating of perceived exertion on Trapezius (TRAP) and Erector Spinae (ES) muscle. On the other hand, walking inclination had significantly affected both right and left ES as well as increased heart rate but decrease psychophysical experience for TRAP and Right ES. Unlike TRAP muscle activity, the subjects rated that their working intensity increased with increasing of walking inclination on ES. The development of mathematical model described that with the increase in load mass, walking distance, and walking inclination, they might increase muscle activity and heart rate as well as psychophysical experience. These results provided guidance to predict the intensity of workers’ muscle activity, heart rate, and psychophysical experience and to create safe working condition as they performed the asymmetrical manual load carrying.